PENGARUH KOMPLEKSITAS TUGAS, TEKANAN KETAATAN DAN SENIORITAS AUDITOR PADA AUDITOR JUDGMENT - Nuarsih, Ni Luh Putu; Mertha, I Made (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
The auditor's judgment is the decision-making audit by an auditor based on ideas, opinions or estimates of information from the audit evidence is influenced by technical and nontechnical factors that the auditor is able to certify the fairness of the financial statements. The complexity of the task, the pressure obedience and seniority auditors are technical and nontechnical factors are considered may affect the auditor's judgment. The purpose of this study was to examine the influence of the complexity of the task, the pressure obedience and seniority auditor in the auditor's judgment. The samples used in the study 35 respondents to the sampling method is non-probability sampling technique is purposive sampling. Methods of data collection is done by questionnaire. This study using multiple linear regression analysis. The results obtained are the complexity of the task, obedience and seniority auditor pressure effect on the auditor's judgment.
Keywords: Auditor’s Judgment, The Complexity of the Task, The Pressure Obedience, Seniority Auditor